Investigation on the Relationship between Product Market Competition with Board Structure and Disclosure Quality (Shahid Bahonar University of Kerman, 2013)
In this study, the influence of product market competition on disclosure quality of companies is investigated, regarding the aspects of strategic effect and governance effect. The data is obtained from 105 companies listed in Tehran Stock Exchange, in the years 1383- 1390. In order to test the hypotheses, Logistic Regression Model is applied. The results from strategic effect showed that there is a meaningful and negative relationship between Herfindohl-Hirschman index and entry costs. This shows there is meaningful and positive relationship between competition and disclosure quality. Findings from governance effect revealed that Herfindohl-Hirschman index and entry costs index have no meaningful effects on the relationship between the board of directors’ independence and the disclosure quality.